Women-headed households and housing location preferences in the informal settlements: What can we learn from Luzira, Uganda?. (September 2022) - Mubiru, Moses Batanda; Nuhu, Said; Kombe, Wilbard; Limbumba, Tatu Mtwangi
Abstract: The decision to move to a preferred location is a phenomenon that women-headed households inevitably grapple with during their housing lifecycle. Choosing a housing location may be determined by several factors. This study sought an in-depth understanding of what drives decisions on preferred housing locations by women-headed households in the Luzira informal settlement of Kampala, Uganda. A qualitative case study design was used, in which in-depth interviews, focus group discussions, and document analysis were employed. Social relations with host households, interactions in the neighbourhood, households' responses to inter-household disputes, household consensus, and informal property market information availability were exhibited as determinants for women-headed household decisions on housing options. This study recommends that policymakers should be aware of the several alternatives and informal channels through which informal property market participants access information on housing opportunities. This can be enhanced by exploiting appropriate technological innovation, such as mobile phones and creating platforms for access and dissemination of housing-related information. More so, key drivers of housing location choices for women should be integral in housing planning. Highlights: Majority of women-headed households are found in the informal settlements in most Sub-Saharan African Cities. Women-heading households primarily utilise social networks to guide their relocations in the informal settlements. Choosing housing locations for women-headed households may be determined by women's lifecycle. Informal property market information is vital for women-headed households to make decisions on relocation.